The girl and the bombardier : a true story of resistance and rescue in Nazi-occupied France - Ankeny, Susan Tate (Diversion Books, a division of Diversion Publishing Corp., 2020)
"A downed World War II bombardier's unfinished memoir and a box of letters from the French girl who saved him sets a veteran's daughter on a journey to craft a true tale of danger, courage, love, and escape."